Is 70Zn(d,x)67Cu the Best Way to Produce 67Cu for Medical Applications? - Nigron, Etienne; Guertin, Arnaud; Haddad, Ferid; Sounalet, Thomas (Frontiers in Medicine, 2021)
The theranostic approach combines diagnostic and therapy towards personalised treatment for patients. Among the different possibilities, associating two radionuclides of the same element is appealing, one for imaging purpose and the other for therapy. Copper offers such a pair of radionuclides with 64Cu (T1/2=12.7 h) allowing PET imaging and 67Cu (T1/2=61.8 h) for targeted beta therapy. If for 64Cu the production route is well defined (a biomedical cyclotron delivering protons on a 64Ni target), this is not the case for 67Cu. Many production routes have been explored using neutrons, charged particles or photons. For charged particles, the main challenge relies on the limitation of 64Cu co-production, even if its real impact on the patient and staff radioprotection needs to be studied and clarified. Within this frame, we have measured 70Zn(d,x) production cross sections for 67Cu and its contaminants up to 30 MeV. Measurements were done using the well-known stacked foils technique on 97.5 % enriched 70Zn homemade electroplated targets. They complement at higher incident energies the only set of data available in nuclear databases. The maximum of the cross section is reached at 23 MeV. Its value, 30 mb, is twice higher than the one obtained with a proton irradiation. With deuterons below 26 MeV, 64Cu production is limited and directly connected to the enrichment of the target. Using a 26 MeV deuteron beam and an enriched 70Zn target, it is then possible to produce high purity 67Cu. Activity of 16.4 GBq can be obtained for 26 MeV and 80 µA beam interacting on a 576 µm thick 70Zn target during 40 hours. The achieved purity is comparable to that obtained using photoproduction. This production route can be of interest for future linear accelerators under development where mA deuteron beams can be available if adequate targetry is developed.